Pengaruh Pendekatan RME terhadap Pemahaman Konsep dan Kemampuan Pemecahan Masalah pada Bangun Siswa Kelas IV MI Plus Nur Rahma Kota Bengkulu - Eci Anita Lestari; Agus Susanta; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to study the effect of the RME approach on conceptual understanding and problem-solving abilities in class IV MI Plus flats at Nur Rahma Bengkulu City. This research is a quantitative research with experimental method. The sample in this study were MI Plus Nur Rahma students from Bengkulu City, totaling 24 students in class IV Darussalam as the control class, and 24 students in class IV Naim as the experimental class. The instruments used in this research were concept comprehension test questions and problem solving ability test questions in the form of essay questions through the pretest and posttest. The data analysis technique in this study was expert validation analysis using Aiken's V, as well as quantitative analysis using the t-test. From the research results it is known that the results of material, construction and language validation are feasible to use in research. Based on the results of hypothesis 1 t test, the value of sig. (2-tailed) 0.00 is smaller than the significant level (α) 0.05, then H0 is rejected and Ha is accepted so that it can be interpreted that there is an effect of the RME approach on the ability to understand mathematical concepts of class IV MI Plus Nur Rahma Bengkulu City. While the t test hypothesis 2 sig. (2-tailed) 0.02 smaller than the significant level (α) 0.05 then H0 is rejected and Ha is accepted. Based on the test, the N-gain score from the application of the RME approach is higher than the conventional approach, so it can be interpreted that there is an influence of the RME approach on the problem solving ability of MI Plus Nur Rahma, Bengkulu City.